PENGARUH ORANG TUA TUNGGAL TERHADAP PEMBENTUKAN SIKAP ANAK DI DESA BONE-BONE KECAMATAN BARAKA KABUPATEN ENREKANG - Pahira Pahira; Ahmad Sultra Rustan; Muhammad Qadaruddin (KOMUNIDA : Media Komunikasi dan Dakwah, 2018)
In every life someone will always be in touch with family. The family is a group that identifies themselves from its members consisting of two or more individuals, whether it is blood relations or legally, but functions in such a way that they consider themselves as family. It's different with single parent families, where there is only one parent, both father and mother. Family care patterns applied by parents in educating children are several ways: authoritarian parenting, muscle-loving parenting, democratic parenting, and caring patterns. The purpose of this study was to determine the influence of single parents on the formation of children's attitudes in Bone-Bone Village, Baraka District, Enrekang Regency. This research is a type of quantitative research that examines the relationship of two variables. The number of samples in this study amounted to 28 people using saturated sampling techniques. The data collection techniques used were questionnaires and documentation. The data analysis technique used is to create a helper table, simple regression analysis, find the Syx value, regression b (Sb) and determine the value of the T test. The results of this study indicate that (1) the care of single parents is in a pretty good category, namely: the average score of 36 which is located in the interval / qualification 39-35 is proven by analyzing the results of questionnaires from 28 respondents, the value of the range of variables X divided by the number of classes variable X. (2) the formation of children's attitudes in Bone-Bone Village, Baraka District, Enrekang Regency is in a pretty good category, namely: an average score of 45 which is located in the 48-45 interval / qualification as evidenced by analyzing the questionnaire of 28 respondents namely the range value variable Y is divided by the number of classes of variable Y. If the value of variable X is higher then the value of variable Y will also be higher. The dominant parenting pattern in this study is authoritative parenting, where care is high in demand and acceptance is also high. (3) Operant Conditioning and Social Learning Theory is very effective in forming children's attitudes. Where this theory is based on habituation and imitation of the environment. The results of the analysis on simple regression statistical tests, namely the t test, obtained the hypothesis test results that that t count (t0)> from 15.33 t table is 2.05. (15,33> 2,05). Thus, H_odi reject and H_adi accept, thus it can be concluded that there is a single parent influence on the formation of children's attitudes in Bone-Bone Village, Baraka District, Enrekang Regency.